2017
DOI: 10.1038/s41598-017-13908-w
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate-induced lipotoxicity alters acetylation of multiple proteins in clonal β cells and human pancreatic islets

Abstract: Type 2 diabetes is characterized by progressive β cell dysfunction, with lipotoxicity playing a possible pathogenetic role. Palmitate is often used to examine the direct effects of lipotoxicity and it may cause mitochondrial alterations by activating protein acetylation. However, it is unknown whether palmitate influences protein acetylation in β cells. We investigated lysine acetylation in mitochondrial proteins from INS-1E β cells (INS-1E) and in proteins from human pancreatic islets (HPI) after 24 h palmita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 72 publications
(87 reference statements)
0
49
0
Order By: Relevance
“…The PA stock solution was diluted in culture medium to which fatty-acid-free BSA had been added in a 1:19 molar ratio to prepare BSA-conjugated PA. Cells were incubated with the BSA-conjugated-PA at 0.5 mM without or with additional 16.7 mM glucose (PA or PAG, respectively) for different times (4,8,16,24, and 48 h).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PA stock solution was diluted in culture medium to which fatty-acid-free BSA had been added in a 1:19 molar ratio to prepare BSA-conjugated PA. Cells were incubated with the BSA-conjugated-PA at 0.5 mM without or with additional 16.7 mM glucose (PA or PAG, respectively) for different times (4,8,16,24, and 48 h).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, recent studies suggested that the metabolites of acyl-CoAs produced by FFAs and glucose can act as the substrates for post-translational modification (PTM) of proteins, such as palmitoylation and acetylation. These PTMs change protein function, which is highly linked to the dysfunction of ␤-cells (23,24). However, the interplay of the above molecular events is not well understood.…”
Section: Graphical Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed most marked hyperacetylation on ES1, IF1, TFEa, 3 lysine acetylation sites on the ADP-ATP translocase 1, isocitrate dehydrogenase [NADP], acyl-CoA thioesterase 8, mMDH2, and GDH1 in INS-1E SIRT3KO cells. Lysine acetylation of TFEa (38), ADP-ATP translocase 1 (39), isocitrate dehydrogenase [NADP] (36), MDH2 (1), and GDH1 (11,13) has been observed previously in other cell types or tissues. Importantly, for several of these enzymes (1,13,36,39), their activity is regulated by lysine acetylation (see also the earlier section of the Discussion).…”
Section: Discussionmentioning
confidence: 64%
“…However, we find that acute glucose stimulation (30 min) is not sufficient to alter the lysine acetylation status of the mitochondrial proteins identified. Lysine acetylation appears regulated mostly on a longer timescale responding to chronic changes in diet rather than rapid fluctuations of nutrients (1, 9, 11, 36).…”
Section: Discussionmentioning
confidence: 99%